Adverse Drug Reactions Resulting From the Use of Chiral Medicines Amoxicillin, Amoxicillin-Clavulanic Acid, and Ceftriaxone: A Mixed Prospective-Retrospective Cohort Study - Kissa W. Mwamwitwa PhD; Elias M. Bukundi Msc; Betty A. Maganda PhD; Castory Munishi MPhil; Adam M. Fimbo PhD; Deus Buma PhD; Eva P. Muro PhD; Wilber Sabiiti PhD; Danstan H. Shewiyo PhD; Morven C. Shearer PhD; Andrew D. Smith PhD; Eliangiringa A. Kaale PhD (SAGE Publishing, 2024)
The use of chiral medicines (possessing center(s) of asymmetric carbon) may cause adverse drug reactions (ADRs). The safety assurance of these medicines is critical. We aimed to evaluate registered and commonly used anti-infective chiral medicines circulating in the Tanzanian market to establish their safety profile to protect public health. A mixed prospective-retrospective cohort study was conducted to assess the safety profile of amoxicillin, amoxicillin-clavulanic acid and ceftriaxone injection. ADRs causality assessment was conducted by using World Health Organization (WHO)-Algorithm criteria. Data were collected from 7 tertiary hospitals: Muhimbili National Hospital (MNH), Kilimanjaro Christian Medical Centre (KCMC), Bugando Medical Centre (BMC), Ligula Referral-Regional Hospital (LRRH), Kitete Referral-Regional Hospital (KRRH), Dodoma Referral-Regional Hospital (DRRH), and Mbeya Zonal-Referral Hospital (MZRH). Data were supplemented by those recorded in the WHO-Vigiflow/VigiLyze database within the same monitoring period. Data were analyzed using STATA version-15. The results were considered statistically significant when P < .05. A total of 2522 patients were enrolled in hospitals: MNH (499), KCMC (407), BMC (396), LRRH (387), KRRH (345), DRRH (249), and MZRH (239). Among those, 1197 (47.5%) were treated with ceftriaxone, 585 (23.2%) amoxicillin and 740(29.3%) amoxicillin-clavulanic acid. Out of those, 102 (4.5%) experienced adverse events (AEs), 49 (48%) were due to ceftriaxone, 37 (36.3%) amoxicillin-clavulanic acid and 16 (15.7%) amoxicillin ( P -value .012). A total of 443 participants from the enrolled and WHO-Vigiflow/VigiLyze database were experienced with ADRs. The ADRs affected mainly gastro-intestinal system 234 (53%), skin and subcutaneous tissue 85 (19%), nervous system 49 (11%), respiratory thoracic 22 (5%), and general disorders 18(4%). In this study, approximately 90% of reported AEs were ADRs possible-related to the monitored medicines, with few plausible and certain. Ceftriaxone injection caused more ADRs. Amoxicillin-clavulanic acid was associated with more ADRs than amoxicillin alone. The safety profile of these medicines is still maintained; however, comprehensive monitoring of ADRs is recommended to improve patient safety and enhance overall treatment outcomes.